Throughfall as an understudied biogeochemical subsidy of nutrients and carbon in the urban water cycle: perspective and a research agenda - Mary G. Lusk (Discover Water)
Abstract Precipitation that moves through tree canopies entrains carbon and nutrients from leaf and bark surfaces. In natural ecosystems, these biogeochemical subsidies to the water cycle are processed by watershed soils before conveyance to fluvial networks. In urban landscapes, however, these subsides of carbon, nitrogen, and phosphorus may bypass watershed soils and instead drip to impervious surfaces and become part of stormwater flows. In this way, urban throughfall may contribute to the carbon and nutrient loads of urban stormwater, with consequences for receiving waters and potential to contribute to eutrophication. Throughfall from urban landscapes is understudied, but the argument is made here that quantifying and characterizing urban throughfall and how it can be contextualized within the urban water cycle are crucial avenues for new research. This paper presents the hypothesis that as in natural ecosystems, throughfall in urban ecosystems is (1) a source of carbon, nitrogen, and phosphorus; (2) will vary in concentration and chemical composition depending on climate, tree species, canopy morphology, and seasonality; and (3) will have impacts on urban ecosystems that have not been investigated. New research should focus on the role of throughfall in constraining urban carbon and nutrient budgets, as well as new research on how throughfall from urban trees contributes to the chemistry of receiving waters.